IMPLEMENTASI PENGENDALIAN INTERNAL TERHADAP SISTEM AKUNTANSI PENGGAJIAN PADA PT. XYZ - Nababan, Natalia; Maula, Kholida Atiyatul (Peneliti.net, 2023)
One that influences the success of the company is the system that is implemented in a company. Payroll accounting system is very influential for the company to support the effectiveness of internal control. This study aims to find out how the payroll system is applied to companies and how internal controls are implemented in the employee salary payment system. The type of research conducted by researchers is qualitative research, which focuses on the payroll accounting system at PT. XYZ and internal control system at PT. XYZ. Data collection techniques were carried out using interviews, documentation, and observation techniques. Data analysis in this study begins with analyzing related functions, supporting documents, accounting records used, network procedures and assessing the effectiveness of internal controls. The results of research at PT. XYZ researchers concluded that internal control in the implementation of the payroll accounting system has been carried out quite well overall because the separation between recording and implementation functions is carried out by dividing the duties and authorities of each employee concerned such as functions, procedures, documents and the necessary records have been formed and have been well coordinated. Internal Control at PT. XYZ is in accordance with SOP (standard operational procedure) this is evident from the implementation of attendance by system not manually. Attendance using an RFID card cannot be manipulated, the placement of the RFID card tap is guarded by a security guard, employees who do not carry an RFID card cannot enter so that cheating in the attendance process does not occur. The documents used consist of payroll, payroll recap, proof of cash out. The network of procedures used which consists of attendance record procedures, procedures for making payroll and wages and procedures for paying salaries and wages, PT. XYZ also has a payroll system flowchart, so that the payroll system can be seen clearly. Basically the system at PT. XYZ has been implemented properly according to the Internal Control System both in the control environment, risk interpretation and company supervision